Research status and development trends of wind-induced vibration technology for photovoltaic support systems - Jiashun Hu; Wenhua Li; Tao Sun; Mingjie Shi; Fan Yang (Journal of Emerging Science and Engineering, 2026)
Against the backdrop of global energy transition, photovoltaic (PV) power generation has witnessed rapid expansion, with China’s newly installed capacity in 2024 accounting for 52.4% of global additions. However, PV support systems face significant wind-induced vibration challenges in complex scenarios. This study systematically reviews advances in wind-induced vibration mitigation technologies for PV supports. First, structural characteristics and failure mechanisms are analyzed for fixed-axis, single-/dual-axis tracking, cable-suspended flexible, and offshore PV support systems. Second, synergistic applications of wind tunnel tests, numerical simulations, and field monitoring are reviewed to reveal nonlinear dynamic mechanisms such as vortex-induced vibration (VIV) and flutter. Third, many important dominant factors, such as aerodynamic parameters, geometric parameters, structural parameters, topographic effects are analyzed in detail. And design strategies such as prestress optimization, damping enhancement, and stiffness assignment are used to mitigate wind-induced vibration response in practice. Current challenges are discussed including unclear dynamic aeroelastic coupling mechanisms, insufficient scaling model similarity, and lack of standards for diverse scenarios. In future, developing high-fidelity multi-physical models, intelligent vibration suppression technologies, and cross-disciplinary frameworks will be emphasized to enhance system robustness and cost-effectiveness under extreme climates, supporting the global scaling of PV deployment.